Male and Female Youth Crime in Canadian Communities: Assessing the Applicability of Social Disorganization Theory - Jacob, Joanna C. (Canadian journal of criminology and criminal justice, 2006)
Despite an increasing awareness of female youths' involvement in criminal activities, few criminology theories and empirical studies account for female youth crime. Social disorganization theory provides an ecological explanation of youth crime rates. This theory is traditionally applied to male youth crime and has been studied predominantly using American data. Social disorganization theory contributes to understanding the social conditions associated with increased crime rates, and it is therefore also useful for understanding female crime. This article examines whether and to what degree social disorganization theory is applicable to male and female youth crime in Canadian communities. Several sources of data are integrated for the analysis of overall, property, and violent youth crime by gender, including the 1996 Canadian Census and the 1996 Canadian Uniform Crime Reporting Survey (UCR). The results lend partial support for the application of this theory at the community level in Canada; however, they also suggest that predictors related to the informal social control of youth crime vary more by type of offence than by gender. (English) [ABSTRACT FROM AUTHOR]